Vacuum-structured electrochromic glazing windows with ultra-low U-Values for building energy savings in all climatic zones - Mi, Wensen; Pu, Jihong; Shen, Chao; Chen, Guozheng; Kalogirou, Soteris A. (My University, 2025)
Electrochromic windows, as a cutting-edge technology, are highly promising for green buildings. However, traditional electrochromic glazing windows have rarely been used in cold and severe cold regions due to their high U-Value. In addition, commercial electrochromic windows regulate the solar transmittance through an absorbing-based mechanism, which may negatively cause secondary solar heat gain and overheating in near-window zones. To address these issues, a vacuum structure with low-emissivity coating was proposed for the WO3-based electrochromic glazing. In this study, a real-scale vacuum-electrochromic (VEC) window is fabricated and evaluated both experimentally and numerically. Experimental results demonstrate that the application of the VEC window in a sunny day can increase the useful daylight illuminance (UDI) by 39 % in 1.5 V state during the working time, whilst reducing the indoor air peak temperature by 3.1 °C and inner glazing surface peak temperatures by 13.6 °C, in full-tinted state. Energy-saving simulation of the VEC window indicate that it is highly promising across all climatic conditions, achieving a building energy saving by 12 %–16 % in five distinct climatic zones of China. These findings indicate that the proposed VEC window is a viable solution for low-energy buildings.
Keywords: Daylight qualities; Electrochromic (EC) glazing; Energy-saving in buildings; Indoor light environment; Vacuum glazing